Memahami Ekspresi Pengalaman Tarian Tubuh Perempuan Dalam Aplikasi TikTok - Deta Indira Puspita; Hapsari Dwiningtyas Sulistyani (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
The problem that women face when expressing their bodies through dance on the TikTok application is getting negative comments from the public without the public understanding about the experiences that women go through when dancing on TikTok. The purpose of this study was to determine the meaning of body expression for women. The method used is qualitative research with Interpretative Phenomenological Analysis technique and uses Theory of Gender and Nonverbal Communication, Theory of Self-Objectification, and Theory of Existentialist Feminism. From this study it was found that the meaning of body expression for women is (1) body expression as a form of self-freedom; (2) body expressions to show sexiness; (3) body expressions to show the beauty of the face and the beauty of the body; (4) expression of the body as self-actualization. The pattern formed from women's experiences concludes that if the freedom and desires that women want to achieve have unconsciously made women objects and subjects. Women can turn things around through full control over their bodies and show their talents, although in the process women become objects by following the wishes of the audience to look attractive.